THE DEVELOPMENT OF UBIQUITOUS LEARNING MANAGEMENT SYSTEM USING IMAGINEERING ON CONSTRUCTION OF MULTIMEDIA: การพัฒนาระบบการจัดการเรียนรู้ยูบิควิตัสด้วยจินตวิศวกรรม เรื่อง การสร้างงานมัลติมีเดีย - Champakul, Pannathat; Innoi, Suwanna; Boonphak, Kanchana (Journal of Education and Innovation, 2020)
The objectives of this research were 1) to develop the Ubiquitous Learning Management System using Imagineering on Construction of Multimedia and 2) to evaluate the quality of the Ubiquitous Learning Management System using Imagineering on Construction of Multimedia, which was developed under the concept of the “System Development Life Cycle: SDLC” consisting of 5 steps; 1) requirement analysis, 2) design, 3) development, 4) testing, and 5) implementation. The informants were three content experts and three web-based learning design experts. The research instruments of this research were 1) Ubiquitous Learning Management System using Imagineering on Construction of Multimedia and 2) quality evaluation form of Ubiquitous Learning Management System using Imagineering on Construction of Multimedia. The statistics for analyzing the data were the average score ( ) and with a standard deviation (S.D.). The results of the research revealed that 1) The Ubiquitous Learning Management System using Imagineering on Construction of Multimedia consisted of 3 modules; the learner’s module, the instructor’s module, and the administrator’s module and 2) the results of the content quality evaluation of the Ubiquitous Learning Management System using Imagineering on Construction of Multimedia was a very high level ( = 4.91, S.D. = 0.29) and the results of the web-based learning design quality evaluation was a high level ( = 4.46, S.D. = 0.50).